2018
DOI: 10.26773/jaspe.180101
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Morphological Characteristics and Body Composition of Football Players in Montenegro

Abstract: A B S T R A C TThe aim of this research was to determine the differences among the top football players of the two best Montenegrin club FC Sutjeska-Niksic and FC Budućnost-Podgorica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
1
0
4

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
6
1
0
4
Order By: Relevance
“…The t-test results showed that the soccer players of the two mentioned clubs have no statistically significant differences according to the variables. Very similar anthropometric characteristics of soccer players were obtained, which shows that soccer players have similar the characteristics and body composition throughout the region (Gardasevic, Bjelica, Popovic, Vasiljevic, & Milosevic, 2018;Corluka & Vasiljevic, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…The t-test results showed that the soccer players of the two mentioned clubs have no statistically significant differences according to the variables. Very similar anthropometric characteristics of soccer players were obtained, which shows that soccer players have similar the characteristics and body composition throughout the region (Gardasevic, Bjelica, Popovic, Vasiljevic, & Milosevic, 2018;Corluka & Vasiljevic, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…The t-test results showed that the soccer players of the two mentioned clubs don't have statistically significant differences by the variables. Very similar characteristics of football players were obtained in the region, which shows that football players have similar the anthropometric characteristics and body composition in the whole region (Gardasevic, Bjelica, Popovic, Vasiljevic, & Milosevic, 2018;Corluka & Vasiljevic, 2018;.…”
Section: Discussionsupporting
confidence: 66%
“…Also, at the variables of triceps skinfold and skinfold of the back, football players of CSC Zrinjski Mostar have shown statistically better values because a smaller number means a better result when the disrupting factor of subcutaneous fat on playing football is taken into account. Very similar characteristics of football players were obtained in the region, which shows that football players have similar the anthropometric characteristics and body composition in the whole region (Gardasevic, Bjelica, Popovic, Vasiljevic, & Milosevic, 2018;Corluka & Vasiljevic, 2018;Bjelica, & Gar-dasevic, 2019;Bjelica, Gardasevic, Vasiljevic, Jeleskovic, & Covic, 2019).…”
Section: Discussionsupporting
confidence: 54%